Bentuk Interaksi Sosial Antar Sesama LANSIA, Pengasuh dan Pendamping di Panti LANSIA Binjai - Irfan Fahreza; Husni Thamrin (Yayasan Literasi Sains Indonesia, 2023)
Social interaction is important in social life, including for the elderly. With the establishment of good social interaction, it will make the elderly feel at home and comfortable living in an elderly home. However, if the social interaction between the elderly, caregivers and companions is not good, it will create a sense of competition and tend to experience sadness in the elderly. The purpose of this research is to find out how the process of social interaction is formed between fellow elderly, caregivers, and companions at the Panti Lansia Binjai and the inhibiting factors of social interaction among fellow elderly, caregivers and companions. This study used a q ualitative research method with a descriptive approach. In collecting data using direct observation methods, interviews and documentation. The data analysis techniques used are data reduction, data display and conclusion. The research results obtained are social interaction processes, namely associative processes in the form of cooperation, accommodation and assimilation and dissociative processes in the form of competition, conflict and quarrels. The social interactions that occur between the elderly, caregivers and companions at the Panti Lansia Binjai can be seen through the establishment of communication in the form of conversation, mutual understanding, cooperation, openness and empathy, mutual support/motivation, having a positive feeling and a sense of similarity with others, where it is an indicator of social interaction.